Domestic entanglements: Family, state, hierarchy, and the Hobbesian state of nature. Issue 2 (31st October 2018) - Levin, Jamie; MacKay, Joseph
Abstract: This article revisits the Hobbesian account of the state of nature and the formation of states, attending to Hobbes's account of the family. Drawing on feminist readings, we find in the Leviathan an account of the family as a natural political community. We contend specifically that a focus on conceptions of family life in the Leviathan, and in works by Hobbes's early modern peers, points to the role of the family as a site of socialisation in the prelude to early state formation and in the formation of political hierarchies more generally – including, we suggest, the formation of international hierarchies. These accounts have thus far been missing from International Relations theory. Contra conventional IR theoretic readings of the Leviathan, the Hobbesian state of nature contains the seeds of both anarchy and hierarchy, as overlapping social configurations. While anarchy emerges clearly in the famous condition of 'war of all against all', hierarchy also exists in Hobbes's depiction of family life as a naturally occurring proto-state setting. On the basis of this contemporary feminist analysis of a classic text, we consider implications for the emerging 'new hierarchy studies' in IR.